The Effectiveness of PBL-Based Multimedia Articulate Storyline and Phet Simulation on Student Learning Outcomes - Purwandari Purwandari; Farida Huriawati; Sinta Kusuma Dewi (LP. Ma'arif Janggan Magetan, 2025)
This study examines the effectiveness of PBL-based multimedia using Articulate Storyline compared to PhET simulation in improving student learning outcomes on the topic of Regular Changing Straight Motion (GLBB). A quasi-experimental design with a pretest-posttest non-equivalent control group was applied to two intact classes: the experimental group used PBL-based Articulate Storyline, while the control group used PhET simulation. The research instrument was a validated multiple-choice test consisting of 10 items, with content validity reaching 86%. Data analysis included normality and homogeneity tests, paired sample t-tests, independent sample t-tests, and N-Gain analysis. Results showed that the experimental class achieved a higher posttest mean score (77.09) compared to the control class (59.57), with N-Gain values of 0.60 (medium) and 0.33 (low), respectively. Effect size analysis also indicated a very large impact of PBL-based Articulate Storyline. These findings suggest that combining multimedia with structured pedagogical approaches, such as PBL, provides more effective learning experiences than exploratory simulations. The novelty of this research lies in directly comparing two popular interactive media within the same experimental framework, offering empirical evidence that PBL-integrated multimedia leads to greater improvements in conceptual understanding of physics.